Ferroelectric-Paraelectric Transition In A Membrane With Quenched-Induced δ-Phase Of PVDF - O. García-Zaldívar (Nature Portfolio, 2017)
Abstract The stabilization of δ-phase of poly(vinylidene fluoride) PVDF in a 14 µm-thickness ferroelectric membrane is achieved by a simple route based on the use of a dimethylformamide (DMF)/acetone solvent, in which the application of external electric field is not required. X-ray diffraction and calorimetric experiments on heating reveal that, at 154 °C, the original mixture between ferroelectric δ-phase and paraelectric α-phase transits to a system with only this latter phase in the crystalline fraction. A gradual and slight increment of amorphous fraction up to the melting at 161 °C is also observed. The existence of δ-phase is corroborated by the occurrence of a broad maximum around 154 °C in dielectric permittivity measurements, as well as the hysteresis loops observed at room temperature. These results suggest a wide thermal window for a stable δ-phase, between room temperature and 154 °C, a subsequent transition into α-phase and the corresponding melting at 161 °C. The broad dielectric maximum observed around 154 °C in dielectric and calorimetric measurements, can be associated with a diffuse ferroelectric-paraelectric transition.